Lost Civilizations: The Secret Histories and Suppressed Technologies of the Ancients by Jim Willis - Alexander, John B. (Journal of Scientific Exploration, 2020)
Lost Civilizations is at once intriguing but also challenging to all conventional wisdom. Perhaps that is as it should be and Willis certainly created an interesting compendium of mysterious archeological events combined with a generous exploration of mythology. Readers of the SSE Journal should know I am not a fan of the “Out of Africa” theory. There have been too many recent discoveries made to support the notion that human life began in a single remote location. We can think of the discovery of the Denisovan that interbred with hominids that did migrate from Africa. What Willis repeatedly points to is apparent DNA anomalies in which samples indicate connections between groups for which there is no logical explanation. As an example, there are traces in Australia that are commensurate with those from South America that must have occurred long before any known contact had happened. While Willis would agree, Lost Civilizations suggests the timelines may be off by many thousands of years, a concept that is hard to integrate into demonstrable history. If somebody built things, where did such previously unknown groups come from? It is in questioning that Willis adds significant value. What do we mean by “lost civilizations” is basic to the book? But more fundamentally he asks how is “civilization” defined? There are multiple definitions and he states that what it means to be civilized does not equate to the organization of villages or cities. Further, if civilizations were “lost” where did they come from and where did they go? How did seemingly thriving communities suddenly cease to exist? Then, why is it that some societies not only physically disappear, but also seem to be erased from the memories of survivors or other groups that may have interacted with them. His examples of lost groups abound and signal a warning to modern society. If previous complex organizations disappeared, often with no immediate trace, could the same thing happen to our current civilization.